Why fertility preservation rates of transgender men are much lower than those of transgender women. Issue 5 (May 2022) - Alpern, Sharon; Yaish, Iris; Wagner-Kolasko, Gal; Greenman, Yona; Sofer, Yael; Paltiel Lifshitz, Dror; Groutz, Asnat; Azem, Foad; Amir, Hadar
Abstract: Research question: What are the fertility preservation rates of transgender women and transgender men, and what are the factors that affect their decision-making? Design: This prospective study included 97 transgender women and 91 transgender men referred to the Gender Clinic of the study medical centre's Endocrinology Institute and to the Gan Meir Community Health Care Centre. The responders completed a 28-item questionnaire during 2018. Results: Most of the transgender women and transgender men wished to parent a child (67.4% and 61.9%, respectively, P = 0.447), but only 40.4% of the transgender women and 5.8% of the transgender men used fertility preservation ( P < 0.001). The main reasons for not pursuing fertility preservation were unwillingness to postpone gender-affirming treatment (58.8% and 74.0%, respectively, P = 0.076), preference to adopt a child (58.8% and 60.9%, respectively, P = 0.818) and cost (44.9% and 60.9%, respectively, P = 0.086). Factors related to the fertility preservation process itself were specifically chosen by transgender men compared with transgender women as the reason for not pursuing this treatment, including distress caused by the fertility preservation technique (60.3% versus 29.3%, respectively, P = 0.006), fear of gender dysphoria caused by hormonal treatment (63.5% versus 28.3%, P = 0.002) and concern over the attitude of medical staff (44% versus 19%, P = 0.027). Conclusions: Fertility preservation rates were considerably lower among transgender men than transgender women, strongly related to the fertility preservation process itself. Finding ways to overcome the obstacles confronted by transgender individuals, especially transgender men, will enhance their future biological parenting.